Catalytic Enantioselective Conjugate Additions of (pin)B‐Substituted Allylcopper Compounds Generated in situ from Butadiene or Isoprene. (20th July 2016) - Li, Xiben; Meng, Fanke; Torker, Sebastian; Shi, Ying; Hoveyda, Amir H.
Abstract: Multicomponent catalytic enantioselective transformations that entail the combination of butadiene or isoprene (common feedstock), an enoate (prepared in one step) and B2 (pin)2 (commercially available) are presented. These processes constitute an uncommon instance of conjugate addition of an allyl moiety and afford the desired products in up to 83 % yield and 98:2 enantiomeric ratio. Based on DFT calculations stereochemical models and rationale for the observed profiles in selectivity are provided.